Tomato spotted wilt virus detection in the potato cultivar Innovator - Salvalaggio, Andrea Eugenia; Bruno, Cecilia Inés; Huarte, Marcelo Atilio; Lopez Lambertini, Paola Maria (Ediciones INTA, 2024)
Tomato spotted wilt orthotospovirus (TSWV) causes important economic losses in potato production. The cultivar Innovator is the most widely used variety for potato industrial processing and the second most extensively grown cultivar in Argentina. The objective of this study was to identify the most suitable tissue sample for TSWV detection in potato cv. Innovator using DAS-ELISA. Tissue samples taken from three different points of the tuber and from the leaves of seedlings originating from two types of sprouts were evaluated for TSWV detection using DAS-ELISA. Detection of TSWV in the tuber tissue was 95%, 86% and 87% for the sample taken below the rose end sprout, below the lateral end sprout, and the pith, respectively. Detection of TSWV in seedlings tissue was 41% and 40% in plants grown from rose and lateral sprouts, respectively. The proportion of positive TSWV samples was higher in samples collected from infected tubers than in those collected from seedlings. Therefore, tuber tissue proved to be suitable for TSWV detection by DAS-ELISA, regardless of the sampling point, because there were no significant differences among points. Sampling the tuber tissue reduces sample collection time since it is not necessary to obtain the progeny plant to analyze the leaves. TSWV caused severe damage in 46% of the infected tubers, which presented symptoms of internal necrosis, reducing the quality and the commercial value of the potato cv. Innovator. The application of an accurate TSWV diagnostic technique is required to achieve an efficient and effective management of this disease in potato. In this context, the inclusion of TSWV detection in the Argentine potato seed certification program would be a positive measure.